A comprehensive review on lncRNA LOXL1-AS1: molecular mechanistic pathways of lncRNA LOXL1-AS1 in tumorigenicity of cancer cells - Yousefnia, Saghar (Frontiers in Oncology, 2024)
Long non-coding RNAs (lncRNAs) are versatile RNAs that regulate various cellular processes, such as gene regulation, by acting as signals, decoys, guides, and scaffolds. A novel recognized lncRNA, LOXL1-antisense RNA 1 (LOXL1-AS1), is dysregulated in some diseases, including cancer, and acts as an oncogenic lncRNA in many types of cancer cells. Upregulation of LOXL1-AS1 has been involved in proliferation, migration, metastasis, and EMT, as well as inhibiting apoptosis in cancer cells. Most importantly, the malignant promoting activity of LOXL1-AS1 can be mostly mediated by sequestering specific miRNAs and inhibiting their binding to the 3´UTR of their target mRNAs, thereby indirectly regulating gene expression. Additionally, LOXL1-AS1 can decoy transcription factors and proteins and prevent their binding to their regulatory regions, inhibiting their mechanistic activity on the regulation of gene expression and signaling pathways. This review presents the mechanistic pathways of the oncogenic role of LOXL1-AS1 by modulating its target miRNAs and proteins in various cancer cells. Having information about the molecular mechanisms regulated by LOXL1-AS1 in cancer cells can open ways to find out particular prognostic biomarkers, as well as discover novel therapeutic approaches for different types of cancer.